MODEL SIMULASI UNTUK MENGAMATI PENGARUH TEGANGAN TARIK-SISA SILINDER AUTOFRETTAGE LARAS SENAPAN - Sahlan, Sahlan (ENERGI & KELISTRIKAN, 2015)
The analysis of autofrettage on fatigue-crack propagation of crack are well documented, that is experimental work shows the effects of positive stress ratio or tensile-minimum stress during the fatigue cycles on the fatigue-crack inition from holes. This simulates model the effect of the residual-tensile stresses at the outside surface of autofrettage cylinders. S-N curves and modified Goodman diagrams are shown for fatigue-crack inition. This allows a tremendous advantage in retarding crack initiation and propagation in the early stages of crack growth, wich accounts for the dramatic increases in useful service life for an autofrettage cylinder compared to a nonautofrettaged cylinder.